THE ROLE OF SEQUENCE MEDIATION ON THE INFLUENCE OF LIVE-STREAMING SHOPPING ATTRIBUTE ON PURCHASE INTENTION - Chan, Syafruddin; Asni, Kurnia (Jurnal Aplikasi Manajemen, 2022)
The urgency of this study is to solve the problem regarding the slow penetration of TikTok Livestreaming shopping; even though the traffic opportunities on TikTok are huge and far outperform any social media application, even if it is compared to applications that existed before TikTok, such as Facebook and Instagram. This study analyzes the factors influencing purchase intention among TikTok users in Indonesia. The number of samples in this study is 180 respondents. A questionnaire with a 5-point Likert scale was used to collect data. The data were processed by using Structural Equation Model (SEM) approach. Of the five direct hypotheses tested, all of them had a significant effect. Thus, we can say Live streaming Shopping Attribute, Products' Trust, and Sellers' Trust are the determinant variables of purchase intention. Even though this research has provided factual information on the contribution of antecedent purchase intention variables, it is necessary to expand the variables considered to support the increase in purchase intention, such as the Guarantee Return Policy and seller pacing. Unlike previous studies that mostly assessed the direct effect of exogen variables on purchase intention used a one-level mediating variable, throughout the author's knowledge, there has been no one to examine the influence of antecedent factors live streaming purchase intention through sequence mediation. This study implies that sellers who use the live streaming channel on TikTok to market their products have to pay serious attention to the quality of the products and guarantee that the products will provide maximum benefits for their buyers.